Electrode/Electrolyte Optimization-Induced Double-Layered Architecture for High-Performance Aqueous Zinc-(Dual) Halogen Batteries - Chengwang Zhou; Zhezheng Ding; Shengzhe Ying; Hao Jiang; Yan Wang; Timing Fang; You Zhang; Bing Sun; Xiao Tang; Xiaomin Liu (Nano-Micro Letters)
Highlights A double-layered protective film based on zinc-based coordination compound and ZnF2-rich solid electrolyte interphase layer has been successfully fabricated on the zinc metal anode via electrode/electrolyte synergistic optimization. The double-layered architecture can effectively modulate Zn2+ flux and suppress the zinc dendrite growth, thus facilitating the uniform zinc deposition. The as-developed zinc-(dual) halogen batteries based on double-layered protective film can present high areal capacity and satisfactory cycling stability.